All-printed capacitors with continuous solution dispensing technology. (17th August 2017) - Ge, Yang; Plötner, Matthias; Berndt, Andreas; Kumar, Amit; Voit, Brigitte; Pospiech, Doris; Fischer, Wolf-Joachim
Abstract: Printed electronics have been introduced into the commercial markets in recent years. Various printing technologies have emerged aiming to process printed electronic devices with low cost, environmental friendliness, and compatibility with large areas and flexible substrates. The aim of this study is to propose a continuous solution dispensing technology for processing all-printed thin-film capacitors on glass substrates using a leading-edge printing instrument. Among all printing technologies, this study provides concrete proof of the following outstanding advantages of this technology: high tolerance to inks, high throughput, low cost, and precise pattern transfers. Ag nanoparticle ink based on glycol ethers was used to print the electrodes. To obtain dielectric ink, a copolymer powder of poly(methyl methacrylate-co-benzoylphenyl methacrylate) containing crosslinkable side groups was dissolved in anisole. Various layouts were designed to support multiple electronic applications. Scanning electron microscopy and atomic force microscopy were used to investigate the all-printed capacitor layers formed using the proposed process. Additionally, the printed capacitors were electrically characterized under direct current and alternating current. The measured electrical properties of the printed capacitors were consistent with the theoretical results.